2011
DOI: 10.4081/cp.2011.e60
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytoma of the Optic Nerve Head-A Diagnostic Dilemma

Abstract: The clinical features, autofluorescence, B-scan ultrasonography, optical coherence tomography and fluorescein angiography of the lesion were described. Multiple investigation modalities are needed to confirm the benign nature of the lesion. Careful evaluation and follow-up is crucial to avoid misdiagnosis and erroneous management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 7 publications
2
23
0
3
Order By: Relevance
“…The SD-OCT findings of melanoma and nevus we observed were consistent with previous large series [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. The heavily pigmented Type 1 optic disc melanocytoma is usually distinguishable from choroidal melanoma and choroidal nevus by funduscopic findings, but SD-OCT may help confirm the diagnosis and identify associated features, such as subretinal fluid, that could affect the clinical course.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The SD-OCT findings of melanoma and nevus we observed were consistent with previous large series [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. The heavily pigmented Type 1 optic disc melanocytoma is usually distinguishable from choroidal melanoma and choroidal nevus by funduscopic findings, but SD-OCT may help confirm the diagnosis and identify associated features, such as subretinal fluid, that could affect the clinical course.…”
Section: Discussionsupporting
confidence: 92%
“…Though the OCT image of that patient was not shown in their study, this patient could have had shared features consistent with our Type 2 optic disc melanocytoma classification, if higher-quality SD-OCT had been performed. Similarly, a case reported by Zalilawati et al [11] was more lightly pigmented and showed less optical shadowing. We propose that the Type 2 appearance may be the result of fewer signal-blocking pigmented cells within the tumor, resulting in less hyporeflective shadow and more visible intralesional structures.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…; Mohmad et al. ). To our knowledge, this is the first report on the FAF changes caused by this tumour compared with other juxtapapillary pigmented tumours.…”
Section: Discussionmentioning
confidence: 98%